Strategies for Enhancing the Quality of Islamic Education Learning - Rachmawati, Reza; Yenuri, Ali Ahmad (Journal of Education and Religious Studies, 2024)
This study aimed to identify: (1) Strategies for Enhancing the Quality of Islamic Education at Qon Gresik Islamic Vocational School; and (2) Factors That May Help or Hinder the Improvement of Islamic Religious Education at Qon Gresik Islamic Vocational School. This study intended to assist the school in providing higher-quality Islamic religious instruction. This study applied a descriptive qualitative methodology, utilizing interviews, observations, and documentation for data collection. The researcher served as the primary instrument in this study. Data were analyzed using descriptive analysis techniques, which involve organizing data for processing, validation, and analysis that occurs simultaneously with data collection. The findings of this study indicated several strategies to improve the quality of Islamic Religious Education, including the use of effective methodologies, structured learning procedures, habitual practices, and extracurricular activities. Based on the fundamental principles of learning applied by educators, students at Qon Gresik Islamic Vocational School showed high enthusiasm for both general knowledge and Islamic studies. These strategies contribute significantly to the school’s efforts in improving the learning experience in the field of Islamic studies. Numerous tactics were employed, including placing a strong emphasis on assignments, enhancing the caliber of human resources—teachers—through training and education, and building up the infrastructure that supports education.